Frequency of HLA-B27 alleles in Brazilian patients with psoriatic arthritis - Bonfiglioli, Rubens; Conde, Roseneide A.; Sampaio-Barros, Percival D.; Louzada-Junior, Paulo [UNESP]; Donadi, Eduardo A. [UNESP]; Bertolo, Manoel B. (Springer, 2008)
This prospective study analyzed the frequency of HLA-B27 and its alleles in 102 Brazilian patients with psoriatic arthritis (PsA). The association of the HLA-B27 alleles with these variants was compared to a control healthy HLA-B27 positive group of 111 individuals. There was a predominance of male gender (59.8%), Caucasian race (89.2%), and negative HLA-B27 (79.4%) patients. Asymmetric oligoarthritis (62.7%) was the most frequently observed clinical PsA subgroup, followed by spondylitis (16.7%), and polyarthritis (15.7%). Male gender and the spondylitis subgroup were statistically associated to the positive HLA-B27, and the oligoarthritis subgroup was associated to the negative HLA-B27. Among the 21 HLA-B27-positive PsA patients, there was a significant prevalence of the HLA-B*2705 allele (90.5%), similar to that observed in the control group (80.2%); HLA-B*2703 and HLA-B*2707 were statistically associated to the control group.
Keywords: B27-human histocompatibility antigen; B*27 alleles; psoriatic arthritis